The Correlation between Self-Regulation and Intention with the Diet Adherence of Adults with Type 2 Diabetes Mellitus - Kusnanto, Kusnanto; Malinda, AyuSeptia; Bahiyah, Khoridatul; Arifin, Hidayat (International Journal of Psychosocial Rehabilitation, 2020)
Success in the management of type 2 diabetes mellitus (T2DM) is determined by dietary compliance, intention and self-regulation. The purpose of this study was to determine the relationship between self-regulation and intention with T2DM diet compliance. A descriptive correlation design with a cross-sectional approach was employed. A total of 108 respondents spread across 5 health primary care centers in Surabaya participated in this study. The independent variables were self-regulation and intention. The dependent variable was diet adherence. The data was obtained through the Treatment Self-Regulation Questionnaire (TSRQ), intention and the Personal Diabetes Questionnaire (PDQ). The data was analyzed using Spearman Rho and ordinal regression with a value of α≤0.05. There was a relationship between self-regulation (p=0.000, r=0.612) and intention (p=0.000, r=0.646) with an adherence to diet among the adults with T2DM. The multivariate test results showed that self-regulation is more dominant (p=0.000) than intention (p=0.014). Self-regulation and intention plays a role in establishing dietary adherence among adults with T2DM. Improved good self-regulation can increase the compliance of patients when they are adhering to the suggested diet. This means that their blood sugar can be controlled properly.